Effectiveness of innovative circular technologies for sustainable rural freshwater supply in Tanzania - Awinia, Christopher S. (Frontiers in Sustainability, 2025)
The present study was conducted in two villages situated in the Ruvu–Wami River Basin upstream catchment area in the Kilosa district. The area was experiencing multiple competing water-use activities exacerbated by climate-change-induced human activities and livestock in-migration. Due to the pressure imposed on hydrological resources, new waterpoints were installed while defective ones were not being repaired. The study was guided by two objectives: (a) to investigate the extent to which new innovative circular technologies improved the overall financial sustainability of freshwater schemes and (b) to determine the extent to which financial sustainability contributed to the technical sustainability and overall sustainability of the rural freshwater supply. This study used Lockwood, Bakalian, and Wakeman’s eight dimensions of sustainability as a conceptual framework to investigate the extent to which innovative circular technologies increased the financial, technical, and overall sustainability of rural freshwater schemes. Data were collected from 131 households through a quantitative semi-structured survey; these data were complemented by qualitative data involving 116 focus group discussions. One key finding is that the innovative circular technologies demonstrated a capability to increase the financial sustainability of water schemes. However, deficiencies in technical sustainability affected this potential, leading to high dissatisfaction and low expectations among water users. This resulted in various failures, which affected the overall sustainability of the innovative circular technologies, showing the close interrelationship between social acceptance and technological and financial sustainability. Six important recommendations have been made, specifically concerning the importance of financial and technical capacity, community ownership, social acceptance, community participation, change management, and procurement standards, which affect the quality of the physical water infrastructure network.